2012
DOI: 10.3319/tao.2011.10.05.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Sea Level Variations Observed by GPS Buoys Using Precise Point Positioning Technique

Abstract: In this study, sea level variation observed by a 1-Hz Global Positioning System (GPS) buoy system is verified by comparing with tide gauge records and is decomposed to reveal high-frequency signals that cannot be detected from 6-minute tide gauge records. Compared to tide gauges traditionally used to monitor sea level changes and affected by land motion, GPS buoys provide high-frequency geocentric measurements of sea level variations. Data from five GPS buoy campaigns near a tide gauge at Anping, Tainan, Taiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Lee et al, 1997;Hocker and Wardwell, 2001;Yu et al 2002b;Dong et al, 2008;Song and Bae, 2011;Kuo et al, 2012) and rivers (e.g. Earle et al, 2005;Emery et al, 2009;Apel et al, 2012) as they are relatively easy to produce and operate.…”
Section: Satellite Location Tracking Buoymentioning
confidence: 96%
“…Lee et al, 1997;Hocker and Wardwell, 2001;Yu et al 2002b;Dong et al, 2008;Song and Bae, 2011;Kuo et al, 2012) and rivers (e.g. Earle et al, 2005;Emery et al, 2009;Apel et al, 2012) as they are relatively easy to produce and operate.…”
Section: Satellite Location Tracking Buoymentioning
confidence: 96%
“…Elle reflète dans un seul paramètre le bruit de la série (y compris le mouvement réel de la bouée) et la différence au niveau du référencement absolu. (KUO et al, 2012 ;FUND et al, 2013). Les résultats ne sont pas encore aussi concluants que ceux obtenus avec le traitement différentiel lorsqu'une station de référence proche est disponible.…”
Section: Figure 4 Les Hauteurs Du Niveau Marin Mesurées Par Le Marégunclassified
“…La technique GNSS présente l'avantage de fournir des données directement rapportées à un système de référence géocentrique mondial alors Thème 3 -Instrumentation, mesures, imagerie et télédétection que les marégraphes fournissent des mesures du niveau de la mer par rapport à la croûte terrestre. Différentes applications des bouées GPS ont déjà été publiées, telles que l'étalonnage des marégraphes côtiers sur des îles éloignées (WATSON et al, 2008 ;TESTUT et al, 2010 ;MARTÍN-MÍGUEZ et al, 2012 ;FUND et al, 2013) et dans des zones au large (BOUIN et al, 2009 ;BALLU et al, 2010 et al, 2011), en utilisant l'ellipsoïde du système de référence géodésique GRS80. Dans un second temps, les positions des bouées ont été estimées par rapport à cette station ILDX à l'aide du module TRACK de la suite logicielle GAMIT/GLOBK permettant le traitement cinématique en mode différentiel.…”
Section: Introductionunclassified
“…PPP has been demonstrated to be a powerful and efficient method for many scientific research and for civilian applications (Li & Zhang 2013), such as crustal deformation monitoring (Savage et al 2004;Hammond & Thatcher 2005;Calais et al 2006;Ohta et al 2008), GPS seismology (Kouba 2003;Avallone et al 2011), earthquake early warning system , GPS buoy (Kuo et al 2012;Fund et al 2013), precise orbit determination of low Earth orbiting satellites (Bock et al 2003) and the precise positioning of mobile objects in land, air and marine (Gao et al 2005;Zhang & Andersen 2006;Geng et al 2010;Alkan & € Ocalan 2013). Kouba (2003) first applied PPP to process the high-rate GPS data for the 2002 Denali Fault earthquake and demonstrated that PPP method using the clock and orbit product of the International Global Navigation Satellite Systems Service (IGS) can be used for detecting seismic waves and satisfy the requirement of the GPS seismology.…”
Section: Introductionmentioning
confidence: 99%